2008
DOI: 10.2215/cjn.03820907
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of Brain Natriuretic Peptides in Patients on Peritoneal Dialysis

Abstract: Conclusions. NT-proBNP have a significant predictive value for survival of CAPD patients and may be of value in guiding risk stratification and potentially targeted therapeutic interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
46
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(52 citation statements)
references
References 61 publications
4
46
1
1
Order By: Relevance
“…Our data also corroborate earlier studies [38, 39] linking an elevated NT-proBNP to systemic inflammation in uremia. This association putatively reflects the close correlations between inflammation and CVD in uremia [13, 23], as well as the fact that myocardial ischemia in LVD is an important inducer of low-grade inflammation [19, 40] that also reflects the mortality risk in these patients regardless of the presence of renal dysfunction [41, 42].…”
Section: Discussionsupporting
confidence: 93%
“…Our data also corroborate earlier studies [38, 39] linking an elevated NT-proBNP to systemic inflammation in uremia. This association putatively reflects the close correlations between inflammation and CVD in uremia [13, 23], as well as the fact that myocardial ischemia in LVD is an important inducer of low-grade inflammation [19, 40] that also reflects the mortality risk in these patients regardless of the presence of renal dysfunction [41, 42].…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies showed that serum TnT and NT-proBNP had predictive value for survival in CAPD patients and that measurement of those cardiac biomarkers may be of value in guiding risk stratification and, potentially, targeted therapeutic interventions (41,42). Our study failed to demonstrate differences between our groups of patients in serum levels of TnT and NT-proBNP.…”
Section: Discussioncontrasting
confidence: 67%
“…First, it is not feasible in dialysis studies to recruit a sample large enough to provide statistical power adequate to assess the individual endpoints of death, cause-specific death, hospitalization, and other events (20). Second, compared with other dialysis populations, our patients are healthier, with a higher protein catabolic rate, a lower incidence of diabetes, and fewer cardiovascular complications (42,43). Lastly, adjustments were not made in our study for other comorbid factors such as obesity, smoking, and exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Observational studies have found that low levels of salt and water removal, independent of residual renal function, are associated with worse survival (1,2). It is not clear, however, whether this association is causal, with excess tissue hydration or expanded plasma volume (PV) accelerating organ dysfunction, or simply evidence that there are difficulties in achieving euvolemia due to confounding factors such as cardiac dysfunction, inflammation, or poor dietary intake (3)(4)(5).…”
mentioning
confidence: 99%